2017
DOI: 10.18203/2320-1770.ijrcog20171964
|View full text |Cite
|
Sign up to set email alerts
|

Emergency cervical cerclage and pregnancy outcomes

Abstract: Background: To evaluate the effectiveness and safety of emergency cervical cerclage in women who presented with advanced cervical changes such as cervical dilatation and bulging foetal membranes.Methods: This is a retrospective study on all women treated with cervical cerclage presented in the late second trimester with advanced cervical dilatation (2 to 4cms) for whom emergency cervical cerclage by McDonald technique.Results: Out of the 24 patients for whom emergency cervical cerclage was performed, three pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 2 publications
(2 reference statements)
0
8
0
Order By: Relevance
“…However, in cases where the procedure is not or cannot be done, high rate of pregnancy loss has been reported. [9][10][11][12][13] Ciavattini et al [9] compared the clinical characteristics of 19 cases that are on bed rest and 18 cases that underwent emergency cerclage, who all received diagnosis at similar weeks. They found that the interval period (16.8±7.9 weeks) up to delivery was significantly higher in the group which underwent emergency cerclage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in cases where the procedure is not or cannot be done, high rate of pregnancy loss has been reported. [9][10][11][12][13] Ciavattini et al [9] compared the clinical characteristics of 19 cases that are on bed rest and 18 cases that underwent emergency cerclage, who all received diagnosis at similar weeks. They found that the interval period (16.8±7.9 weeks) up to delivery was significantly higher in the group which underwent emergency cerclage.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, the authors found pregnancy loss in 2 (2/15; 13.3%) cases, preterm labor rate as 80% and excessively premature preterm labor rate as 20%. Prasad et al [12] analyzed 24 cases which underwent emergency cerclage in their study, and reported pregnancy loss 12.5%, and preterm labor rate 42%.…”
Section: Discussionmentioning
confidence: 99%
“…During cerclage the prolapsed membranes must be placed back in the uterine cavity before the procedure to avoid high risk of iatrogenic PPROM. This is accomplished least traumatically by placing the patient in the lithotomy position with a steep Trendelenburg tilt, combined with the administration of tocolytics 3 . Urinary catheterization can also help to reposition the membranes in the uterus.…”
Section: Discussionmentioning
confidence: 99%
“…17 A review done on all women treated with CC in the late second trimester with advanced cervical dilatation for whom emergency CC by McDonald method were performed, showed that for post emergency CC the results for extension of pregnancy, live births and neonatal survival is better. 18 A study of 158 women under emergency CC showed that emergency CC is successful in extending pregnancy and recuperating neonatal result in patients having cervical deficiency. 19 The results of 14 patients having twin pregnancies were studied with substantial cervical dynamics undergoing cerclage showed that the average duration between cerclage placement and giving birth was 71.1 days indicating patients carrying twin pregnancies with advanced cervical changes may profit by therapeutic cerclage.…”
Section: Introductionmentioning
confidence: 99%
“…32 A study on 24 women treated with emergency CC in the late second trimester having advanced cervical dilatation showed that pregnancy continuation, live births and neonatal survival results are better in post emergency CC. 33 A study including 158 women having emergency CC due to cervix dilatation and bulging membranes in mid-trimester showed that having emergency cerclage provided live infants births with 82.28% success. 34…”
Section: Introductionmentioning
confidence: 99%